GnRH agonist and hCG (dual trigger) versus hCG trigger for final follicular maturation: a double-blinded, randomized controlled study. Issue 7 (20th June 2020) - Haas, J; Bassil, R; Samara, N; Zilberberg, E; Mehta, C; Orvieto, R; Casper, R F
Abstract: STUDY QUESTION: Does co-administration of GnRH agonist and Human chorionic gonadotropin (hCG; dual trigger) in IVF cycles improve the number of mature oocytes and pregnancy outcome compared to hCG alone? SUMMARY ANSWER: Using the dual trigger for final follicular maturation increases the number of oocytes, mature oocytes and number of blastocysts (total and top-quality) compared to triggering with hCG alone. WHAT IS KNOWN ALREADY: hCG is used at the end of controlled ovarian hyperstimulation as a surrogate LH surge to induce final oocyte maturation. Recently, based on retrospective studies, the co-administration of GnRH agonist and hCG for final oocyte maturation (dual trigger) has been suggested to improve IVF outcome and pregnancy rates STUDY DESIGN, SIZE, DURATION: A single center, randomized controlled, double-blinded clinical trial between May 2016 and June 2018 analyzed by intention to treat (ITT). PARTICIPANTS/MATERIALS, SETTINGS, METHODS: One hundred and fifty-five normal responder patients were randomized either to receive hCG or dual trigger for final oocyte maturation. Data on patients age, BMI, AMH, number of oocytes retrieved, number of metaphase 2 (MII) oocytes, zygotes and blastocysts, clinical pregnancy rate and live birth rate were assessed and compared between the dual trigger group and the hCG group. We performed a planned interim analysis after the recruitment of 50% of the patients. Based on the totality of outcomes at the interim analysis we decided to discontinue further recruitment. MAIN RESULTS AND THE ROLE OF CHANCE: One hundred and fifty-five patients were included in the study. The age (36 years versus 35.3 years P = NS), BMI (24 kg/m 2 versus 23.7 kg/m 2 ) and the AMH (20.1 pmol/l versus 22.4 pmol/l) were comparable between the two groups. Based on ITT analysis, the number of eggs retrieved (11.1 versus 13.4, P  = 0.002), the MII oocytes (8.6 versus 10.3, P  = 0.009), total number of blastocysts (2.9 versus 3.9, P  = 0.01) and top-quality blastocysts transferred (44.7% versus 64.9%; P  = 0.003) were significantly higher in the dual trigger group compared to the hCG group. The clinical pregnancy rate (24.3% versus 46.1%, OR 2.65 (1.43–1.93), P  = 0.009) and the live birth rate per transfer (22% versus 36.2%, OR= 1.98 (1.05–3.75), P  = 0.03) were significantly higher in the dual trigger group compared to the hCG group. LIMITATIONS, REASONS FOR CAUTION: None. WIDER IMPLICATIONS OF THE FINDINGS: The enhanced response observed with the dual trigger might lead to better IVF outcomes were it used more widely. STUDY FUNDING/COMPETING INTEREST(S): The study was funded by TRIO Fertility. There are no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: ClinicalTrials.gov identifier: NCT02703584 DATE OF TRIAL REGISTRATION: March 2016 DATE OF FIRST PATIENT'S ENROLLMENT: May 2016